(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the early outcomes of laparoscopic surgery in the treatment of colon cancer. Materials and Methods: A descriptive study was conducted on 42 patients diagnosed with colon cancer who underwent laparoscopic colectomy with lymph node dissection at Can Tho Oncology Hospital from January 2023 to October 2024. Results: The mean age of the participants was 56.2 ± 12.6 years, with males accounting for 69%. The most common tumor location was the sigmoid colon (54.8%). The mean operative time was 158.5 ± 43.6 minutes, and the mean estimated blood loss was 59.4 ml. The average number of harvested lymph nodes was 16.6 ± 4.2. The overall complication rate was 21.4%, including surgical site infection (9.5%) and postoperative ileus (16.7%), no cases of anastomotic leakage or mortality were recorded. The mean postoperative hospital stay was 7.1 ± 0.8 days. Conclusion: Early outcomes of laparoscopic surgery for colon cancer treatment show that this is a safe and feasible method, with low complication rates and a reliable maximum number of harvested lymph nodes..